Basal polyphagan beetles in mid-Cretaceous amber from Myanmar: biogeographic implications and long-term morphological stasis. Issue 1894 (16th January 2019) - Cai, Chenyang; Lawrence, John F.; Yamamoto, Shûhei; Leschen, Richard A. B.; Newton, Alfred F.; Ślipiński, Adam; Yin, Ziwei; Huang, Diying; Engel, Michael S.
Abstract : The origin and early evolutionary history of polyphagan beetles have been largely based on evidence from the derived and diverse 'core Polyphaga', whereas little is known about the species-poor basal polyphagan lineages, which include Scirtoidea (Clambidae, Decliniidae, Eucinetidae, and Scirtidae) and Derodontidae. Here, we report two new species Acalyptomerus thayerae sp. nov. and Sphaerothorax uenoi sp. nov., both belonging to extant genera of Clambidae, from mid-Cretaceous Burmese amber. Acalyptomerus thayerae has a close affinity to A. herbertfranzi, a species currently occurring in Mesoamerica and northern South America. Sphaerothorax uenoi is closely related to extant species of Sphaerothorax, which are usually collected in forests of Nothofagus of Australia, Chile, and New Zealand. The discovery of two Cretaceous species from northern Myanmar indicates that both genera had lengthy evolutionary histories, originated at least by the earliest Cenomanian, and were probably more widespread than at present. Remarkable morphological similarities between fossil and living species suggest that both genera changed little over long periods of geological time. The long-term persistence of similar mesic microhabitats such as leaf litter may account for the 99 Myr morphological stasis in Acalyptomerus and Sphaerothorax . Additionally, the extinct staphylinoid family Ptismidae is proposed as a new synonym of Clambidae, and its only included species Ptisma zasukhae is placed as incertae sedis within Clambidae.